Prevalence and pattern of contraceptive uptake among adolescents in an internally displaced camp, North Central, Nigeria - Oluwatosin R. Ilori; Adenike Olugbenga-Bello; O. Goodman; Aishatu Babankudi; Rilwan Oladejo (AOSIS, 2023)
Background: Internally displaced Persons are marginally sidelined in many areas of life , reproductive health issues inclusive. There is a need to know the prevalence and pattern of contraceptive use among this vulnerable group of people. Objective: This study determined the prevalence and pattern of contraceptive uptake among internally displaced adolescents in North-Central Camp, Abuja, Nigeria. Methods: a descriptive cross-sectional study, among 403 adolescents using semi-structured questionnaires. Results:The mean age of the respondents was 19.53±6.4 years and 21.34 ± 7.34 years at first birth. Awareness about FP was high, (483, 95.0%), however, only 169 (41.9%) ever used a family planning method, while 82(20.3%) were current users, 72 (42.6%) of the 169 ever users admitted to have used pills, while 44(53.7%) of the 82 current users were using condom only. One third, 160(39.7%), were pregnant, while 78(19.4%) of those pregnant were unintentional, therefore the unintended pregnancy rate was 19.4%.Bivariate analysis revealed that respondents' use of contraceptive was significantly related to religion (0.001), ethnic group (0.001), marital status (0.001), family type (0.001), and educational attainment (0.001). While respondents' knowledge of contraceptive was significantly associated with age (P0.00000001), educational level (P 0.002), and ethnic group (P 0.001).Conclusion: The prevalence of contraceptive use among respondents was 20.3%, while 41.9% ever used a method. Pill was the major Family planning method ever used, while condom was mostly used by the current users.